FAKTOR KELUARGA (POLA ASUH, SOSIAL EKONOMI, KEHARMONISAN) TERHADAP KENAKALAN REMAJA PUTRI (SEKS BEBAS) DI SMA NEGERI 12 SURABAYA - Sugiarti Sugiarti (Akademi Kebidanan Griya Husada Surabaya, 2017)
Adolescence is a period of transition from childhood to adulthood. Juvenile delinquency is an anti-norm adolescent action that applies in society. From a preliminary study conducted on 14 young women at SMAN 12 found 8 people had had free sex and from the data obtained from the BK office of SMA 12 Surabaya in 2014 there were 1 young woman who dumped her baby in a school toilet because of KTD. Family factors are a major factor in juvenile delinquency. This study aims to describe family factors (parenting, socio-economic, harmony) towards juvenile delinquency (free sex) in Surabaya 12 Public High School. Method: The research method used was descriptive, the population of which there were 418 people with a sample size of 81 people using the systematic random sampling technique. The processed data is analyzed by creating a frequency table master and cross tabulation is made then conclusions are made. Results: The results of the study showed that the majority of adolescents did not have juvenile delinquency, namely 73 people (90.12%), the majority with democratic parenting 47 people (58.02%), the majority with socioeconomic levels over 61 people (75.31%) and with a harmonious family of 70 people (86.42%). In the majority of cross tabulations that do juvenile delinquency with permissive parenting, lower socio-economic and family that are not harmonious Discussion: It can be concluded from this study that family factors influence juvenile delinquency. Therefore parents should be wiser in applying parenting to their teenagers so that they can establish better communication so as to create a harmonious life between children and parents. As well as parents more increase again in giving supervision and guiding children in behaving and behaving.